Analysis of voltage sag in an industrial distribution system of the provincial electricity authority of Thailand - Chiangkakun,N. (2015)
This paper presents a calculation of voltage sag magnitude, area of vulnerability spectrum and method for SARFI-indices due to a fault in distribution system of Provincial Electricity Authority of Thailand. Voltage sag is related to power quality problems and reliability of utility. Analysis of voltage sag will help utilities to determine and predict the area of vulnerability in distribution system. The SARFI-indices can reveal a reliability of utility to industrial customers. For this paper, voltage sag analysis is performed by using DIgSILENT Power Factory programs for short circuit simulations and presentation of area of vulnerability spectrum. Distribution network is modeled by using actual network data with geographic information system (GIS). © 2012 IEEE.